Prey dynamics as a buffer: enhancing copepod resilience to ocean alkalinity enhancement - Amrita Bhaumik; Giulia Faucher; Merle Henning; Cédric L Meunier; Maarten Boersma (Environmental Research Letters)
Ocean alkalinity enhancement (OAE) aims to counteract climate change by increasing the ocean’s carbon storage capacity through the addition of alkaline substances into seawater. However, this process alters seawater chemistry, increasing total alkalinity and pH, which can directly influence marine organisms’ metabolic activities or indirectly impact them through changes in prey availability and quality. This study disentangled the OAE-driven factors that might influence zooplankton physiology. We assessed the direct effects of altered chemistry on the copepod, Temora longicornis, and the indirect effects through changes in the phytoplankton prey, Rhodomonas salina . We cultured the prey under OAE conditions and used it to feed copepods to investigate the indirect effects. We found that OAE negatively impacted prey growth but improved its nutritional quality, thereby offsetting the direct negative impact of OAE on the copepod. These findings regarding OAE’s impact on prey-predator dynamics contribute to a deeper understanding of how OAE may influence zooplankton communities.